This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: 1 Tuesday, October 27, 2009 Note: there is t and t’-=-→ --=-→ e at0t 0tbt'e at'dt' e atxt e0x0 0tbt'e at'dt' | | x-= +-→ = -+ --e atxt x0 0tbt'e at'dt xt e atx0 e at0tbt'e at'dt' 51 IF b(t)=b constant multiply by -a/-a = 1-= -= ---= --=---0tbt'e at'dt' b0te at'dt' b a0te at'd at' bae at'0t bae at e0 So for constant b = -+ ---- → = --- -xt e atx0 e at bae at 1 xt e atx0 ba1 e at52 2...
View Full Document
This note was uploaded on 01/08/2010 for the course COT 3502 taught by Professor Hawkins during the Fall '08 term at University of Florida.
- Fall '08